An exploration of subjective well-being in children and adolescents with ADHD in South Africa during the Covid-19 pandemic - Eloff, Irma F. (University of Pretoria, 2023)
Mini Dissertation (MEd (Educational Psychology))--University of Pretoria, 2022.